Dental Caries Status of Institutionalized Orphan Children from Jammu and Kashmir, India - Tangade, Pradeep; Batra, Manu; Tirth, Amit; Ravishankar, TL; Shah, Aasim F; Pal, Sumit (International journal of clinical pediatric dentistry, 2016)
It has been well documented that the absence of family support influences the general and oral health of the children. Factors that lead to the development of disease at a given point in time are likely to have their roots in a complex chain of environmental events that may have begun years before. A number of studies have examined the relationship between dental caries and material deprivation and found a positive association between them. Though orphans contribute to 2% of world's population, literature regarding their oral health status is very scarce. This study was carried out with the aim to assess the dental caries status of institutionalized orphan children from Jammu and Kashmir. A total of 1,664 children that included 1,201 boys and 463 girls from registered orphanages in the state of Jammu and Kashmir were included in the study. Written informed consent was obtained prior to the start of the study; decayed, extracted, filled teeth (deft)/ decayed, extracted, filled surface (defs) and decayed, missing, and filled teeth (DMFT)/decayed, missing, and filled surface (DMFS) indices were used to assess the caries status of primary and permanent dentition. Multiple choice, close-ended questionnaires were administered to assess the oral hygiene habits, knowledge, and dietary behavior of orphan children prior to examination. The study subjects were divided into three groups according to the age of ≤ 6, 7 to 11, and ≥12 years. Results showed that caries prevalence in primary dentition was higher in subjects' ≤6 years of age where the prevalence was 50.9%; in subjects 7 to 11 years of age, the prevalence was 25.2%. Caries prevalence in permanent dentition within the age group 7 to 11 was 69.1%, while in subjects' ≥12 years, the prevalence was 66.2%. Use of toothbrush was the most prevalent method of cleaning the teeth in both the genders, while toothpaste was reported to be the most prevalent material to be used for tooth cleaning followed by tooth-powder. Highest caries prevalence was seen in the subjects using datun sticks as a method to clean their teeth (80.5%). Shah AF, Tangade P, Ravishankar TL, Tirth A, Pal S, Batra M. Dental Caries Status of Institutionalized Orphan Children from Jammu and Kashmir, India. Int J Clin Pediatr Dent 2016;9(4):364-371.